Bricolage as an Intervention to Resource Constraints in Social Entrepreneurship – A Systematic Literature Review (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Bricolage is at the very heart of entrepreneurship. However, research on Bricolage in the context of social entrepreneurship is still in its early stage. The role of bricolage during resource constraint situation and resource acquisition methodology in social entrepreneurship needed in depth understanding. Objective: To identify key outcomes of bricolage & theories involved in bricolage in social entrepreneurship. Methodology: A systematic literature review of English articles on social Entrepreneurship and the intersection of the Bricolage concept from electronic databases since 2020. Search terms included Social entrepreneurship, social entrepreneur, Bricolage, Bricoleur. Study Selection: Only scholarly peer reviewed articles, with bricolage and social entrepreneurship were included. Data Extraction: Independent extraction of articles by 2 authors using predefined data fields was carried out. Results: 1306 records were identified through database searching. Articles with full text, scholarly peer - reviews articles in English Language only were included in the study. After several inclusion and exclusion criteria. We used articles at the intersection between bricolage and social entrepreneurship. Conclusion: The paper contributes significantly to the existing literature by conducting a systematic review of extant works. The study identified theories, types and consequences of bricolage used in social entrepreneurship. The paper concludes by setting up the agenda for future researchers in the field. There is a wide scope to study on bricolage in social entrepreneurship.